Embracing The Digital Era: A Literature Review On Digital Technologies For Arabic Language Learning Among Young Learners - Dalimunthe, Singgar Mantahari; Asmaniah, Neli; Habsi, Syifa Pauzia; Nopriansyah, Beri; Mela, Desriliwa Ade (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The rapid development of digital technology has had a significant impact on the world of education, including Arabic language learning. Arabic, which plays an important role in education and religion, is now increasingly in demand among young people who are familiar with digital technology. This study uses a qualitative approach with library research methods to explore various technologies that can improve the effectiveness of Arabic language learning for young people. The inclusion criteria in this study include academic literature published between 2015 and 2024 that discusses the application of digital technology in Arabic language learning, while studies that are not relevant to the context of language education or are not technology-based are excluded. The results show that the use of mobile applications such as Duolingo and Memrise, online learning platforms such as Coursera and EdX, and interactive technologies such as Augmented Reality (AR) and Virtual Reality (VR) not only increase learning flexibility but also strengthen students' immersive and participatory experiences. In addition, the use of educational games, Artificial Intelligence (AI), and social media contributes to increased motivation and independence in learning. Critically, this study highlights that the success of technology implementation is greatly influenced by the readiness of digital infrastructure, teacher competence, and the learning culture in Indonesia, which still tends to be conventional. Thus, the integration of technology in Arabic language learning needs to be accompanied by teacher training, curriculum adaptation, and supporting policies in order to be implemented effectively and sustainably.